A Comparative Study of Nickel Electrodeposition Using Deep Eutectic Solvents and Aqueous Solutions. (10th September 2015) - Abbott, Andrew P.; Ballantyne, Andrew; Harris, Robert C.; Juma, Jamil A.; Ryder, Karl S.; Forrest, Greg
Graphical abstract: Highlights: Facile electro-deposition of bright Ni is possible from DES electrolytes at elevated temp. and high concentration. Harder Ni deposits are obtained from DES than from aqueous electrolytes. Similar deposition rates are measured despite the higher viscosity of the DES. High temp. speciation of Ni 2+ in DES determines morphology of deposit. Ni deposition in DES shows a levelling effect when compared to Ni plating in aqueous electrolytes. Abstract: Metal electrodeposition using ionic liquid electrolytes and deep eutectic solvents is now well known but to our knowledge for electrolytic deposition of metals such as nickel no direct comparison has thus far been drawn between deposition using aqueous solutions and DES under otherwise identical conditions. In the current study it is shown that nickel deposition can be carried out with similar deposition rates in aqueous and ionic media despite the significant differences in viscosity and conductivity. It is, however, shown that in ionic media the morphology of the deposits is markedly different from that achieved using a Watts nickel bath and that one aspect of these differences manifests itself in significant increase in the coating hardness. It is proposed that the observed morphology differences occur due to the variations of nickel speciation in each electrolyte environment.